The Impact of Social Media on Adolescent Mental Health: A Meta-Analysis - Gabrielle, Tiffany; Mathius Sonne; Niama Nina Indolo (Scientia Psychiatrica, 2024)
Introduction: The proliferation of social media has raised significant concerns about its potential effects on the mental health of adolescents. This meta-analysis aims to provide a comprehensive assessment of the existing research on the relationship between social media use and various mental health outcomes in adolescents. Methods: A systematic search of electronic databases (PubMed, PsycINFO, Scopus, Web of Science) from January 2018 to June 2024 was conducted to identify relevant studies. Studies were included if they examined the association between social media use and mental health outcomes in adolescents (aged 10-19) and reported quantitative data. Effect sizes were calculated and pooled using random-effects models. Results: A total of 45 studies (N = 153,285 adolescents) met the inclusion criteria. The meta-analysis revealed small but significant associations between increased social media use and increased depressive symptoms (r = 0.12), anxiety (r = 0.10), and loneliness (r = 0.15). Furthermore, a significant negative association was found between social media use and self-esteem (r = -0.08). The analysis also identified several moderators of these effects, including gender, age, and type of social media platform. Conclusion: The findings of this meta-analysis suggest that increased social media use is associated with a range of negative mental health outcomes in adolescents. However, the effects are small, and the relationship is complex, with several moderating factors. Further research is needed to understand the mechanisms underlying these associations and to develop effective interventions to mitigate the potential negative effects of social media on adolescent mental health.